2019
DOI: 10.1007/s12264-019-00413-5
|View full text |Cite
|
Sign up to set email alerts
|

SCN9A Epileptic Encephalopathy Mutations Display a Gain-of-function Phenotype and Distinct Sensitivity to Oxcarbazepine

Abstract: Genetic mutants of voltage-gated sodium channels (VGSCs) are considered to be responsible for the increasing number of epilepsy syndromes. Previous research has indicated that mutations of one of the VGSC genes, SCN9A (Nav1.7), result in febrile seizures and Dravet syndrome in humans. Despite these recent efforts, the electrophysiological basis of SCN9A mutations remains unclear. Here, we performed a genetic screen of patients with febrile seizures and identified a novel missense mutation of SCN9A (W1150R). El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 34 publications
(46 reference statements)
0
27
0
3
Order By: Relevance
“…100 Furthermore, OXC was also able to inhibit sodium currents of hNav1.7 and caused a hyperpolarizing shift in the activation and inactivation properties of Nav1.7 channels. 101 Thus, although both CBZ and OXC are able to block Nav current, the effect can be achieved with a lower concentration with OXC. 102 It should be noted that the differences in the analgesic properties of CBZ and OXC may in part be related to actions on other voltage-gated ion channels, such as voltage-gated calcium channels (VGCCs), 103,104 and thus, their ability to modulate several neurotransmitter systems involved in pain modulation (for review, see Tomi c et al 105 ).…”
Section: Studies On Heterologously Expressed Channelsmentioning
confidence: 99%
“…100 Furthermore, OXC was also able to inhibit sodium currents of hNav1.7 and caused a hyperpolarizing shift in the activation and inactivation properties of Nav1.7 channels. 101 Thus, although both CBZ and OXC are able to block Nav current, the effect can be achieved with a lower concentration with OXC. 102 It should be noted that the differences in the analgesic properties of CBZ and OXC may in part be related to actions on other voltage-gated ion channels, such as voltage-gated calcium channels (VGCCs), 103,104 and thus, their ability to modulate several neurotransmitter systems involved in pain modulation (for review, see Tomi c et al 105 ).…”
Section: Studies On Heterologously Expressed Channelsmentioning
confidence: 99%
“…Pain disorder mutations with GoF are related with diseases such as erythromelalgia (EMI), small-fiber neuropathy (SFN) and paroxysmal extreme pain disorder (PEPD), and mutations with LoF are related with congenital insensitivity to pain (CIP) (Cen et al, 2017). Epilepsy studies such as Zhang S. et al (2020) showed mutations with GoF phenotype: W1150R, N641Y, and K655R mutations ( Table 5). Being that, after treatment with OXC (120 µmol/L), N641Y and K655R reduced sodium current and decreased the opening time of the channel, while W1150R did not alter that (Zhang S. et al, 2020).…”
Section: Nav17mentioning
confidence: 99%
“…Epilepsy studies such as Zhang S. et al (2020) showed mutations with GoF phenotype: W1150R, N641Y, and K655R mutations ( Table 5). Being that, after treatment with OXC (120 µmol/L), N641Y and K655R reduced sodium current and decreased the opening time of the channel, while W1150R did not alter that (Zhang S. et al, 2020). However, in a study conducted by Yang et al (2018), one of the patients presented generalized tonic-clonic Faster recovery from inactivation More susceptible to clonic and tonic seizures induced by electrical stimulation (mice) Enhanced persistent current (Singh et al, 2009;Zhang S. et al, 2020) I1901fs C-terminal…”
Section: Nav17mentioning
confidence: 99%
See 2 more Smart Citations